Cultural formulation of diagnosis: state of the art - Rohlof, H.; Groen, S.; van Dijk, R.; Knipscheer, J. (Nervenheilkunde, 2017)
In 1994, the Outline for Cultural Formulation (OCF) was included as a supplement to the DSM-IV. The OCF was developed as a tool to help care providers gain more insight in cultural factors which might be relevant while diagnosing mental problems of patients with cultural backgrounds that differ from the care provider´s. More than twenty years after publication, the query is justified whether the OCF actually serves the purpose it was intended for, and whether any adjustments are needed. By means of a literature search an answer is sought to these questions. The main conclusion is that reactions of professionals to the cultural formulation were positive and that it has managed to find its way into education, and, to a lesser extent, into clinical practice. However, evaluative and effect studies have been mostly lacking in the first period. Recent research has shown more favourable effects.
Keywords: Mental health care; diagnosis; cultural formulation; cultural interview